Portrait of an OT artist: Using Mindfulness to find Life Balance - Lydia Royeen (Scholarworks @ WMU, 2016)
Lynn Davies, a Canadian-based occupational therapist, understands the skill set and practice required to employ a balanced work/play/leisure routine, even for an occupational therapist. Occupational therapists can easily foster this balanced routine for clients; however, they may fall short of adopting this balanced routine in their own lives. Lynn uses art and mindfulness strategies to strive for a meaningful routine. Balancing her work as a therapist and her engagement in art is an ever-evolving orchestra, as she has a passion for both.